Faktor-Faktor yang Mempengaruhi Keandalan Instalasi Listrik - Taryana Taryana; Cris Kuntadi; Yayuk Suprihartini; Rini Sadiatmi (Dinasti Review, 2022)
Abstract: Previous research or relevant research is very important in a research or scientific article. This article reviews the factors that affect the Reliability of Electrical Installations, namely Short Circuit Protection, Leakage Current Protection, and Grounding Systems, which is a literature study on human resource management. The purpose of writing this article is to build a hypothesis on the influence between variables to be used in further research. The results of this literature review article are: 1) Short circuit protection affects the reliability of electrical installations; 2) Leakage current protection affects the reliability of electrical installations; and 3) The land system affects the Reliability of the Electrical Installation. Abstrak: Riset sebelumnya atau riset yang relevan sangat penting dalam suatu riset atau artikel ilmiah. Artikel ini mereview faktor-faktor yang memengaruhi Keandalan Instalasi Listrik , yaitu Pengaman Hubug Singkat, Pengaman Arus Bocor dan Sistem Pertanahan , merupakan suatu studi literatur manajemen sumber daya manusia. Tujuan penulisan artikel ini guna membangun hipotesis pengaruh antar variabel untuk digunakan pada riset selanjutnya. Hasil artikel literature review ini adalah: 1) Pengaman hubung singkat berpengaruh terhadap Keandalan Instalasi Listrik ; 2) Pengaman arus bocor berpengaruh terhadap Keandalan Instalasi Listrik ; dan 3) Sistem pertanahan berpengaruh terhadap Keandalan Instalasi Listrik.